2015
DOI: 10.1186/s12884-015-0625-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study

Abstract: BackgroundMaternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique.MethodsThis study used qualitative research methods including key informant interviews with stakeholders from the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 18 publications
3
72
0
7
Order By: Relevance
“…Factors pointed by this review affecting the use of the CDK are not very different from barriers and facilitators found in other studies assessing the utilization of other health services within ANC [7, 29, 30]. In several African and Asian countries, it is a common practice among pregnant women to seek for traditional medication or TBAs as first line providers since they perceive facility birth as less convenient.…”
Section: Discussionmentioning
confidence: 62%
“…Factors pointed by this review affecting the use of the CDK are not very different from barriers and facilitators found in other studies assessing the utilization of other health services within ANC [7, 29, 30]. In several African and Asian countries, it is a common practice among pregnant women to seek for traditional medication or TBAs as first line providers since they perceive facility birth as less convenient.…”
Section: Discussionmentioning
confidence: 62%
“…Health programmes should involve communities by disseminating information about the importance of early ANC. Other studies reported that fear of witchcraft [31,32], religion[34], education [31,34] and economic security[31,32] are associated with access to ANC. Educating and economically empowering women could improve early access to ANC and utilization of health services.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the proposal of this study, which does not only allow to assess the prevalence of HIV and STI, in a population group of pregnant women, but also to verify whether the norms for the diagnosis and treatment of these infections are followed. The analysis of this situation will allow the adjustment of the standards of conduct of health personnel, if these are not in accordance with those recommended at national and international level [87][88][89][90][91][92][93][94][95].…”
Section: Resultsmentioning
confidence: 99%